INVENTARISASI JAMUR PENYEBAB PENYAKIT DAUN PALEM RAJA (Roystonea elata Bartr.) TAMAN KOTA MEDAN - Sarah Valentina N.; Mukhtar Iskandar Pinem; Lahmuddin Lubis (Universitas Sumatera Utara, 2014)
Research on title the utility inventarization fungus which was caused diseases on leaf Roystoneaelata Bartr. in Medan city garden. The research aim to know and to inventary fungus that causedleaf Roystonea elata Bartr. diseases in Medan city garden. The research conducted at Laboratory ofPlant Pathology Faculty of Agriculture, University of North Sumatera with altitude ±25 m asl. Thisresearch used survey method. The Result of this research showed that fungus caused leaf Roystoneaelata Bartr. diseases which in A. Yani garden’s and G. Mada garden’s was Bipolaris sp.,Pestalotiopsis palmarum, Curvularia spp., Fusarium sp. whereas Roystonea elata Bartr. which inLapangan Merdeka garden’s and Teladan garden’s was Bipolaris sp., Pestalotiopsis palmarum,Curvularia spp.Keywords : inventarization, fungus, Roystonea elata Bartr